The Influence of Company Size, Profitability, And Sales Growth on Capital Structure - Wella Melananda; Wa Ode Irma Sari (Journal of Social Research, 2024)
This study investigates the impact of firm size, profitability, and sales growth on capital structure in the context of mining companies listed on the Indonesia Stock Exchange for the period of 2019-2022. The study aims to provide insights into the factors that influence the capital structure decisions of mining companies in Indonesia. The data used in this study is secondary data obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The sample size for this research is 11 companies, selected using purposive sampling technique. The findings of the study reveal that firm size has a significant effect on capital structure, indicating that larger firms tend to have a higher level of debt in their capital structure. However, the study finds no significant relationship between profitability and sales growth with capital structure. These results suggest that mining companies in Indonesia may prioritize firm size when making capital structure decisions, while profitability and sales growth may not be significant factors in determining their capital structure. The implications of these findings are important for mining companies in Indonesia, as they provide insights into the factors that influence their capital structure decisions. By understanding the impact of firm size on capital structure, companies can make informed decisions about their debt financing and equity financing options. Additionally, the findings suggest that profitability and sales growth may not be significant factors in determining capital structure, which may help companies to focus on other factors when making capital structure decisions.